Effectiveness of Coping Through Audio Visual Education of J. Watson's Caring Concept Model on Reducing Anxiety Pre Percutaneous Coronary Intervention (PCI) of Cad Patients in the Hospital - Endah Tri Rahayuningrum; Tri Ismu Pujianto; Rusnoto Rusnoto (Indonesian Journal of Global Health Research, 2025)
Coronary Heart Disease (CHD) is the leading cause of death globally, including in Indonesia. One of the procedures to treat CHD is Percutaneous Coronary Intervention (PCI), but this action often causes significant anxiety in patients. Unmanaged anxiety can worsen the physical and mental condition of patients. This study aims to analyze the effectiveness of audio-visual education based on the Caring Jean Watson concept in reducing anxiety in pre-PCI patients at Dr. Loekmonohadi Hospital, Kudus. The study design was a quasi-experiment with a "nonequivalent control group design", involving 40 patients divided into two groups: intervention (Watson's audio-visual caring education) and control (conventional education). Anxiety levels were measured using the Hospital Anxiety and Depression Scale (HADS) before and after the intervention. The data obtained before being analyzed was tested using the Shapiro-Wilk test to ensure that the data was normally distributed, then a parametric paired T-test was carried out to see the difference in anxiety between before and after being given education. The results showed a significant decrease in anxiety in the intervention group, where 45% of patients reached normal anxiety levels and only 10% still experienced severe anxiety. In contrast, in the control group, 70% of patients remained at severe anxiety levels. The paired T-test statistical test produced a p-value of 0.000 (p < 0.05 ), indicating a significant difference before and after education. Caring-based audio-visual education has been shown to be effective in reducing pre-PCI patient anxiety.